Implementasi Teknologi Hybrid Ecodry Serta Penerapan Keselamatan Dan Kesehatan Kerja (K3) Pada Usaha Kerajinan Eceng Gondok Dalam Program TJSL Nawacita - Ismail, Taufik; Insaniah, Cita; Jauhari, Jauhari; Algifari, M Zakky; Fedryansyah, Muhammad (International Journal of Demos (IJD), 2023)
AbstractThe Pesona Walahar Creative Destination (Nawacita) program is implemented by PT Pertamina Patra Niaga Fuel Terminal Cikampek in Walahar Village, Klari District, Karawang Regency. Walahar Village has a water area that originates from the Citarum River. Water hyacinths grow in abundance and are difficult to control, becoming part of environmental problems. Various work programs from 2020 to 2023 with the aim of reducing water hyacinth have been implemented, including reforestation of the Citarum watershed area and regular cleaning, formation of environmental awareness groups and Proklim, innovative use of water hyacinth as the main raw material for biogas energy sources, as well as innovation for craft raw materials. Utilizing water hyacinth as raw material for crafts is an effort to reduce water hyacinth which has added economic value. Before processing water hyacinth crafts, they need to be dried first. The previous process of drying water hyacinth used the heat of sunlight for 1000 kg of wet water hyacinth which could be dried in stages for up to 30 days and the results were not yet effective, and the stages of applying preservatives and coloring caused health risks so a solution was needed to increase the effectiveness of the drying process by creating technology. Hybrid Ecodry innovation for drying and mixing preservation and coloring materials. Hybrid Ecodry (capacity 10 Kg), every 1000 Kg of wet water hyacinth can increase the effectiveness of drying results over time by up to 50%, in terms of results of successfully dried water hyacinth the effectiveness increases to 31.25%, the economic value of dry water hyacinth increases to IDR 656,000 or 31.25%, and the economic value of water hyacinth products increased 31.25% to IDR 7,872,000. The social impact is increasing awareness and capacity of water hyacinth craftsmen in using PPE (Personal Protective Equipment) and APAR (Light Fire Extinguishing Equipment), as well as reducing the risk of health decline, while for the environmental impact the amount of water hyacinth waste reduction has increased to reach 24,000 kg/year.Keywords: Hybrid Eco Dry, Crafts, Water Hyacinth, HSE AbstrakProgram Pesona Walahar Creative Destination (Nawacita) yang dilaksanakan oleh PT Pertamina Patra Niaga Fuel Terminal Cikampek di Desa Walahar, Kecamatan Klari, Kabupaten Karawang. Desa Walahar memiliki wilayah perairan yang bersumber dari Sungai Citarum. Eceng gondok tumbuh banyak dan sulit dikendalikan menjadi bagian dari permasalahan lingkungan. Berbagai program kerja dari tahun 2020 hingga 2023 ini dengan tujuan untuk mereduksi eceng gondok telah dilaksanakan yang diantaranya penghijauan area DAS Citarum dan pembersihan secara berkala, pembentukan kelompok sadar lingkungan dan Proklim, inovasi pemanfaatan eceng inovasi eceng gondok untuk bahan baku utama sumber energi biogas, serta inovasi untuk bahan baku kerajinan. Pemanfaatan eceng gondok menjadi bahan baku kerajinan menjadi upaya reduksi eceng gondok yang memiliki nilai tambah ekonomi. Eceng gondok sebelum diproses kerajinan perlu dikeringkan terlebih dahulu. Proses pengeringan eceng gondok sebelumnya mengadalkan panas sinar matahari untuk 1000 Kg eceng gondok basah dapat dikeringkan secara bertahap hingga 30 hari dan belum efektif hasilnya, serta dalam tahapan pemberian bahan pengawet dan pewarnaan menimbulkan resiko kesehatan sehingga diperlukan solusi untuk meningkatan efektifitas dalam proses pengeringan dengan diciptakannya Teknologi Inovasi Hybrid Ecodry untuk pengeringan dan pencampuran bahan pengawetan serta pewarnaan. Hybrid Ecodry (kapasitas 10 Kg), setiap 1000 Kg eceng gondok basah dapat meningkatkan efektifitas hasil pengeringan secara waktu mencapai 50%, secara hasil eceng gondok yang berhasil dikeringkan efektifitasnya meningkat menjadi 31,25%, Nilai ekonomi eceng gondok kering meningkat menjadi Rp 656.000 atau 31,25%, dan nilai ekonomi produk eceng gondok meningkat 31,25% menjadi Rp 7.872.000. Dampak sosial meningkatnya kesadaran dan kapasitas pengrajin eceng gondok dalam penggunaan APD (Alat Pelindung Diri) dan APAR (Alat Pemadaman Api Ringan), serta menurunnya resiko penurunan kesehatan sedangkan untuk dampak lingkungan meningkatnya jumlah reduksi limbah eceng gondok mencapai 24.000 Kg/tahun.Kata kunci: Hybrid Ecodry, Kerajinan, Eceng Gondok, K3